Psicopatología de las compulsiones de lavado en el trastorno obsesivo-compulsivo: no todos los pacientes lavan por los mismos motivos - García-Soriano, Gemma; Carrió, Carmen; Belloch, Amparo (Revista de Psicopatología y Psicología Clínica, 2016)
Abstract: Psychopathology of washing compulsions in obsessive-compulsive disorder: Not all patients wash for the same reasons. Obsessive-compulsive disorder (OCD) is a heterogeneous disorder in terms of the contents of obsessions and compulsions. Washing, being one of the most frequent compulsion modalities, has been associated with different variables such as: physical or mental contamination fears, fears associated with negative affect (including disgust) and the loss of control, a high level of perfectionism, or the avoidance of a sense of dirtiness or incompleteness. In this study, these variables are examined through the descriptive analysis of the psychopathological symptoms and treatment responses of three patients with OCD and washing rituals as their main diagnosis. Both the clinical analysis and the evaluation through self-reports reflect the motivational heterogeneity associated with a same symptom expression, washing, and suggest the need to consider these variables in the individualized treatment of each patient. Resumen: El trastorno obsesivo-compulsivo (TOC) es un trastorno heterogéneo en cuanto al contenido de las obsesiones y compulsiones. El lavado, una de las compulsiones más frecuentes, se ha asociado a diferentes variables como: el miedo al contagio físico o mental, el miedo al afecto negativo y a la pérdida de control, un elevado perfeccionismo o la evitación de la sensación de suciedad o de inacabado. En este trabajo se examinan estas variables a través del análisis descriptivo de la sintomatología psicopatológica y la respuesta al tratamiento de tres pacientes con diagnóstico principal de TOC que realizan rituales de lavado. Tanto el análisis clínico como la evaluación a través de autoinformes muestran la heterogeneidad motivacional que subyace a una misma expresión sintomática, el lavado, y sugieren la necesidad de tener esta variable en cuenta en el abordaje terapéutico individualizado de cada paciente.